PSYCHOLOGICAL WELL-BEING PEREMPUAN PENGEMUDI ONLINE DI KOTA PADANG - Rizki Syafitri; Wanda Fitri; Urwatul Wusqa; Siska Novra Elvina (JURNAL SIPAKALEBBI, 2022)
This study aims to determine the psychological well-being of female online drivers in the city of Padang. Women who work as online drivers experience a lot of pressure, including unfavorable views from the community, coming home late at night, getting fictitious orders, etc. Even so, they still do work as online drivers. The method used in this study is a qualitative description, the researcher subjects are women who work as online drivers in the city of Padang, totaly 25 people. In collecting data using observation and interviews by applying snowball sampling technique. The results of the study found that female online drivers in the city of Padang had positive and good psychological well-being. This is evidenced by having good self-acceptance, being able to build good relationships with others, having autonomy, having long and short-term life goals, getting support from family and closest friends, being able to be independent and controlling emotions, and being able to carry out personal growth such as improving discipline, increase potential and master application skills in order to get a lot of points. This is in accordance with Ryff's theory of psychological well-being. So, it can be said that female online drivers in Padang City can enjoy their work as online drivers despite the many obstacles they go through at work.